The materiality of divine agency - Pongratz-Leisten, Beate (Studies in ancient Near Eastern records ;, 2015)
This volume explores two topics of contemporary critical interest, agency and materiality, in the context of their intersection with the divine. Specific case studies, emphasizing the ancient Near East but including treatments also of the European Middle Ages and ancient Greece, draw on a broad range of written and pictorial sources to elucidate the nature and implications of this intersection.